The value of brunt scoring in predicting the short term outcome of non-alcohlic steatohepatitis - Hewavisenthi, S.J.de S.; Pathmeswaran, A.; de Silva, H.J. (Wiley Blackwell Scientific Publications, 2004)
BACKGROUND: Brunt scoring is currently used in the grading and staging of liver biopsies in non-alcoholic steatohepatitis (NASH). Its value in predicting the outcome of patients following modifications in lifestyle, the cornerstone of management in NASH, needs evaluation. OBJECTIVES: To determine whether Brunt grades correlate with Aspartate transaminase (AST) and Alanine transaminase (ALT) levels, and outcome following lifestyle modifications in NASH. METHOD: In a prospective study from May 1999 to May 2003 the biopsies of 79 patients diagnosed as having NASH were assigned 3 necroinflammatory grades based on the Brunt system. The mean serum transaminase values at presentation for each necroinflammatory grade were compared using ANOVA. 77/79 patients were given advice on lifestyle modifications and then followed up for a median 2.5 years. The time taken for serum transaminases to return to normal was correlated with the necroinflammatory grades, AST and ALT values at presentation using Kendall tau b. RESULTS : The mean AST and ALT values (IU/L) in the three necroinflammatory grades were - grade 1:62.4 and 102:1, grade 2: 87.6 and 139.4 and grade 3: 90.9 and 164.5. There was a significant difference in the AST and ALT values between grades 1 and 2, and grades 1 and 3, but not between grades 2 and 3. In 51/77 patients serum transaminases returned to normal levels after a median 6 months (range 3– 14 months). There was no significant correlation between the time taken for serum transaminases to return to normal and the transaminase values or necroinflammatory grades at presentation. CONCLUSION: Brunt grading correlates with both AST and ALT levels. However, neither necroinflammatory grades nor serum transaminase values at first presentation are predictors of the duration to normalization of liver enzymes in NASH patients managed with life style modifications
Poster Session Abstract (No.05), 14th Asian Pacific Association for the Study of the Liver(APASL), December 11-15, 2004, New Delhi, India
Keywords: Non-alcoholic Fatty Liver Disease; Non-alcoholic Fatty Liver Disease-diagnosis; Biopsy; Aspartate Aminotransferases; Alanine Transaminase